THE COVID-19 PANDEMIC – A CHALLENGE FOR CRISIS COMMUNICATORS - Želimir Kešetović; Muris Mujanović (Bezbednosni Dijalozi, 2022)
Crisis communication is an integral and very important part of crisis management which can significantly affect the effectiveness of overall efforts to prevent, mitigate and/or manage each crisis situation. This applies to all crises and disasters, especially those related to human health in general, epidemics and pandemics in particular. Despite the scenario of a possible pandemic being at the top of the risk register of a large number of countries, the whole world was unprepared and surprised by the COVID-19 pandemic crisis that hit humanity in early 2020. Due to a number of characteristics of the COVID-19 pandemic itself and the local/national but also global media and social environment, this pandemic has been and still is (since it is not over yet) a serious challenge not only for operational crisis managers (especially epidemiologists, but also overall national health systems) but also for crisis communicators. Factors that have made crisis communication particularly difficult in this crisis are: the unreliability/uncertainty of expert knowledge, unclear national strategies/approaches to pandemics, widespread infodemia (myths and conspiracy theories), and various national and global attempts at political instrumentalization of the crisis. All of this is happening in circumstances where trust in experts, the health care system and government institutions in general and political leaders in particular has been severely weakened (“post trust society”). Based on previous experiences, it can be concluded that there is no best and universally applicable crisis communication strategy in this crisis. What is certain, however, is the fact that this crisis represents an opportunity to learn in many segments, including crisis communication. In every state/society/community it is important to analyse particular segments of the public and understand their perception of the situation (e.g., young AfroAmericans in the US). In addition to the general rules and principles of effective crisis communication, the following factors are very important in its design: starting points and value systems, the interests and needs of those who manage the crisis; the pandemic strategy chosen; country development level, the educational level of the population, the availability of ICT; the characteristics of public opinion (critical or subject to manipulation); predominant national culture, mentality, values, tradition.